Living with Precarious Legal Status in Canada: Implications for the Well-Being of Children and Families - Bernhard, Judith K.; Goldring, Luin; Young, Julie; Berinstein, Carolina; Wilson, Beth (Refuge: Canada’s Journal on Refugees, 2007)
This study focused on the effects of precarious status on the well-being of fifteen participants with particular attention to their attempts to claim services, their feelings of belonging and sense of social support, and the effects of parents’ status on children. It investigates ways in which the status of one family member can affect the well-being of the entire family. Those who had children reported that the family’s status disadvantaged their children, whether they were Canadian or foreign-born, as parents’ status was used to justify denying children rights to which they are entitled by international, national, and provincial laws. The paper challenges approaches to citizenship and immigration status that fail to consider the implications of legal status for a person’s primary social units and networks.